How Green Brand Love Mediates Green Brand Loyalty in Eco-Friendly Cosmetics ? - Purwianti, Lily; Ariyanto , Hepy Hefri; Fidia, Fidia (Universitas Muhammadiyah Sorong, 2025)
In the increasingly competitive eco-friendly cosmetics market, building sustainability‐based consumer loyalty presents an important challenge. This study aims to analyse the effects of brand popularity (BP), brand authenticity (BAUNT) and green brand trust (GBT) on green brand love (GBL), as well as their direct and indirect effects on green brand loyalty (GBLOY). A quantitative design was adopted, involving 412 female consumers of green cosmetic products in Batam, Indonesia, selected using purposive sampling. Data were analyzed using SmartPLS 4 to evaluate the measurement and structural models, while SPSS was used for descriptive statistics. Results indicate that BP, BAUNT and GBT have significant positive effects on GBL and GBLOY. Furthermore, GBL partially mediates the relationships between BP, BAUNT and GBT with GBLOY. These findings demonstrate that both cognitive (brand popularity, authenticity, and trust) and affective (green brand love) processes jointly shape consumer loyalty in sustainability‐oriented markets. The study contributes theoretically by extending Commitment–Trust Theory in the context of green cosmetics branding and offers practical insights for persuading environmentally conscious consumers through authentic, trustworthy, and emotionally engaging brand strategies.